MINYAK ATSIRI KULIT BUAH JERUK MANIS DENGAN MENGGUNAKAN METODE DESTILASI UAP - Rizkiyah; Yelmira Zalfiatri; Angga Pramana (Fakultas Pertanian Universitas Riau, 2024)
Essential oil from sweet orange peel can be obtained through a distillation process. Steam distillation is one of the methods commonly used to extract essential oils. This study aims to find the best distillation time for the physicochemical properties of essential oil from sweet orange peel. The study was conducted experimentally using a completely randomised design (CRD) method with 5 treatments and 3 replications to obtain 15 experimental units. The treatments in this study were P1 (2 hours), P2 (3 hours), P3 (4 hours), P4 (5 hours), and P5 (6 hours). The results of the study were analysed statistically using analysis of variance (ANOVA). The DMRT test was carried out at the 5% level if the F count was greater than the F table. Yield, refractive index, specific gravity, colour, and solubility in alcohol were the parameters analysed in this study. The results showed that distillation time affected the results analysed. P5 was the best treatment in this study, with a distillation time of 6 hours, producing a yield of sweet orange peel essential oil of 0.64%. This treatment has a refractive index of 1.4745, a specific gravity of 0.8119 g/ml, a colour L (brightness) of 31.48, a* (redness) of -0.2800, b* (yellowness) of 2.82, and a solubility in clear alcohol of 1:1.